Assessing the Complexity of a Recovered Design and its Potential Redesign Alternatives - Urbanic, R. J.; ElMaraghy, W. H. (Cranfield University Press, 2009)
Reverse engineering techniques are applied to generate a part model where there is no existing documentation or it is no longer up to date. To facilitate the reverse engineering tasks, a modular, multiperspective design recovery framework has been developed. An evaluation of the product and feature complexity characteristics can readily be extracted from the design recovery framework by using a modification of a rapid complexity assessment tool. The results from this tool provide insight with respect to the original design and assists with the evaluation of potential alternatives and risks, as illustrated by the case study.
Organised by: Cranfield University
Keywords: Product Complexity; Design Recovery; Redesign